A CORRELATION OF EMOTIONAL INTELLIGENCE AND POSITIVE PSYCHOLOGY - Kahveci, Müedin (International Scientific Journal Vision, 2018)
Emotional intelligence is defined as ability of individuals to recognize and understand their own and other’s people emotions, and use that knowledge to manage their thinking and behavior (Mayer and Salovey, 1997). The one thing that is unavoidable to consider in terms of emotional intelligence is importance of its development in person’s life. With that in mind, the awareness of development of emotional intelligence since the earliest age had raised. Emotional intelligence is a term that has been in the last fifteen years are often mentioned and popular in the psychology as well as in the wider general public. The first research of emotional intelligences is closely connecte two authors, John Mayer and Peter Salovey, which are inherently scientifically methodological, but systematically, developed models and instruments for evaluating emotional intelligence. In the field of measurement Individual differences in emotional intelligence are most common recall two approaches: a) selfassessment of one’s own abilities and b) examining emotional intelligence with the test of the test. These cognitions served as a basis for many programs for the development of emotional skills and skills for different groups of people (children and adults) who are creating around the world. Because of the effort to discover and highlight the positive characteristics of individuals through emotional intelligence is represented in a positive psychology.